Effect of CuO/MgO Ratio on the Drug Delivery Kinetics of CuO-MgO-P2O5-SiO2-CaO-ZnO Glasses - Bains, Rupinderjeet (My University, 2017)
Copper and Magnesium based bioactive glasses with chemical composition (15- x)CuO-xMgO-10P2O5-60SiO2-10CaO-5ZnO (2.5 ≤ x ≤ 12.5) were prepared by mixing raw materials in the organic form of cetyltrimethylammoniumbromide (CTAB), CaO, ZnO, SiO2, P2O5, MgO and CuO by sol-gel technique. The pore size of the as prepared MBGs lies between 5.8 and 8.4nm whereas the surface area varies from 98.22 to 442.41 cm2/g. The MBGs were loaded with the anticancerous, anti-inflammatory, antibiotic and antibacterial drugs, doxorubicin, Ibuprofen, amoxicillin and vancomycin, respectively. The increasing copper content influenced the bioactive as well as drug loading and release kinetics of diffferent drugs at different concentrations. In addition to this, the cytotoxicity assays were conducted for MG63 human osteosarcoma cell line. The prepared MBGs have high surface area and mesopore volume, high drug loading efficiency and controllable drug release.
Master of Technology -Materials Science and Metallurgy
Keywords: Bioactive glass; cytotoxicity; drug loading; mesoporous